TINGKAT KEPUASAN MAHASISWA TERHADAP UTILITAS DI JURUSAN TEKNIK SIPIL POLITEKNIK NEGERI SRIWIJAYA - Puryanto Puryanto; Zainuddin Muchtar; Sudarmadji Sudarmadji (PILAR, 2012)
Under conditions of rapid change, then every organization needs to act as an adaptive consequence of internal and external environmental changes that occur with an orientation to provide the best service to its customers. Various efforts were made Department of Civil Engineering Politeknik Negeri Sriwijaya is an effort to improve service and convenience to the students by building facilities and infrastructure and curriculum programs. This study aims to determine the extent of student satisfaction to the utilities in the Department of Civil Engineering Politeknik Negeri Sriwijaya, to know the attributes or indicators that need to be improved, and learned attributes or indicators that need to be maintained in giving satisfaction to the students of the Utilities Department of Civil Engineering at Politeknik Negeri Sriwijaya. The research is an applied research, a systematic study of a problem with the objective to be used immediately for specific purposes. This study is also an observational study is the observation of the studied object, trying to gather data from a phenomenon that has emerged. The study using 168 samples with Stratify Proportional Random Sampling technique. Variables studied variables in the Service Quality Dimensions that are used as indicators of Quality of Service. Dimension is divided into two main parts: Variable Interest ; a student's perception of the utility in POLSRI expectations, and satisfaction variables ; a student's perception of the utility's performance in POLSRI. The variables studied are variable in the dimension of service quality : Tangible, Reliability, Responsiveness, Assurance, and Empathy. Analytical techniques used Importance-perfomance is also called the Gap Analysis. Gap Analysis results will be described with Cartesian Diagram, by calculating the average of the interest assessment which is a dimension of ServQual and satisfaction of each variable or attribute. The results showed that the level of student satisfaction of utility in the Department of Civil Engineering Politeknik Negeri Sriwijaya amounted to 3.274 from 5.0 Scale. Level of student interest to utilities amounted to 4.390 5.0 Scale. Rate Gap students in the utility is equal to -1.116 5.0 Scale. Above findings obtained in this study, then there are some suggestions that can be given, is to optimize the handling of student satisfaction better, Conduct periodic customer satisfaction research, and the tendency of "operations oriented" to move on "service oriented", and understanding of social conditions and consumer culture in South Sumatra, may also be considered in formulating a strategy that can be given excellent service to students.